Resources for preventing sickness absence due to low back pain - Rolli Salathé, C.; Melloh, Markus; Mannion, A.; Tamcan, O.; Müller, U.; Boos, N.; Elfering, A. (2012)
Background: After an episode of non-specific low back pain (LBP) some individuals fail to return to work. The factors leading to such LBP-related sickness absence are not yet fully understood. Aims: To identify individual resources, over and above the already established predictors, for preventing LBP-related sickness absence in a population-based sample of workers experiencing an episode of LBP. Methods: Cohort study with 1-year follow-up. Participants were from a working population who reported an episode of acute or subacute LBP at baseline. Four potential resources-life satisfaction, doing sports, job satisfaction and social support at work-were examined for their incremental value in predicting sickness absence over and above baseline sickness absence and fear-avoidance beliefs about work. Results: In all, 279 workers participated in the study. All four resources showed an inverse relationship with regard to sickness absence. A multiple regression analysis revealed that life satisfaction as a resource protected against sickness absence, when controlling for established risk factors. Job satisfaction and social support at work minimized the influence of sickness absence at baseline and at 1-year follow-up. Conclusions: In a non-clinical working sample of individuals experiencing an acute/subacute episode of LBP, life satisfaction was a unique predictor of sickness absence after 1 year. Prevention in the occupational setting should not only address common risk factors but also occupational and individual resources that keep workers satisfied with life despite having LBP. © The Author 2012. Published by Oxford University Press on behalf of the Society of Occupational Medicine. All rights reserved.